THE STUDENTS’ PERCEPTION TOWARDS USING MOBILE APPLICATION FOR BUSINESS ENGLISH LEARNING - Herlina Herlina; Santoso Santoso (Universitas PGRI Palembang, 2022)
This paper reviews about The Students’ Perception towards Using Mobile Application for Business English Learning that the writer consider, may contribute to the overall effectiveness of the learning process of Business English Learning. The focus of the study is to know the implementation of Using Mobile Application for Business English Learning. The problem of this research is about “What is student’s perception mobile application for Business English Learning? In line with focus of research is to know student’s perception toward the mobile application for Business English Learning. It is necessary to describe the weaknesses and strengths in Using Mobile Application for Business English Learning into the mobile application: WhatsApp and Google Classroom. In this study, the writer used qualitative method, the writer provided questionnaires. The questionnaire was given by the writer to 39 students. They were told by the writer to answer the questions to find out the students perception toward English business learning using Mobile Application. Based on the findings and discussion, using the mobile application (Google classroom & WhatsApp) in Business English learning online classroom is the best choice due to pandemic COVID-19. In term of students perceptions toward using mobile application the writer concluded that it clearly shows the students have perceptions in English learning during the pandemic COVID-19 while using mobile application (Google classroom & WhatsApp); such as learning English using a mobile application makes it easier to learn and they understand learning using a mobile application, but sometimes students understand better if they learn face-to-face. In term of the students perceptions toward strengths and weaknesses in using mobile application for English learning, the writer conclude that it clearly shows that the strengths and weaknesses of using mobile applications for learning English, most of the answers of students in the strengths of a mobile app is to simplify the learning process due to the covid-19 pandemic. The weaknesses is that learning will be difficult when the internet connection has problems and slow.